Genetic enhancement of mustard for seed yield & its sustainability (Journal of Oilseed Brassica, 2026)
The contribution of rapeseed-mustard to the total oilseed acreage and production in India is 23.7% and 26% respectively, during the year 2012-13. The yield of rapeseed-mustard was 1176 kg/ha as compared to 955 kg/ha of total oilseeds. Indian mustard (Brassica juncea (L.) Czern & Coss.) accounts for about 80 % of the 6.3 m ha area under rapeseed- mustard crops in the country